EVOLUSI TVET DALAM SATU DEKADE: ANALISIS PEMODELAN TOPIK MENGGUNAKAN LDA - Yuhefizar; Ronal Watrianthos (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research examines the changing focus of Technical and Vocational Education and Training (TVET) studies from 2013 to 2023. The researchers analyzed 298 academic articles using a method called Latent Dirichlet Allocation (LDA) to identify main themes. They found five key areas of TVET research: developing skills for employment, TVET policies and management, using technology in TVET, training TVET teachers, and addressing gender and fairness in TVET. The study shows that research on technology in TVET grew the most, increasing from about 20% of all studies in 2013 to 27% in 2023, with a sharp rise after 2019. Meanwhile, research on skills and employment decreased from about 28% to 22%, suggesting researchers are now looking at these issues in a more holistic way. The researchers also noticed that different themes started to overlap more over time. For example, studies combining technology and skills increased from about 5% in 2013 to 15% in 2023. These changes reflect how TVET research is adapting to global economic and technological shifts, showing a growing understanding that TVET challenges are interconnected.